2019
DOI: 10.5194/ica-adv-2-8-2019
|View full text |Cite
|
Sign up to set email alerts
|

User Behaviour in the Wild: Analysing Naturalistic Log Data of a Pedestrian Navigation App

Abstract: Abstract. Knowledge about real-life user behaviour is an important factor for the design of navigation systems. Prompted by the observation that users tend to use our campus navigation app in unexpected ways, we present a naturalistic study of navigation logs. The data set consists of sensor and interaction data from over 4600 sessions, collected over a span of several months from hundreds of users. In our analysis, we demonstrate how the core concepts from navigation literature, i. e. wayfinding and locomotio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Based on earlier studies, we know that users tend to carry their device in their hands for the majority of time when navigating [ 30 ]. By applying the device placement classifier to naturalistic navigation data, we can further investigate how exactly this changes over time during a typical navigation session.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on earlier studies, we know that users tend to carry their device in their hands for the majority of time when navigating [ 30 ]. By applying the device placement classifier to naturalistic navigation data, we can further investigate how exactly this changes over time during a typical navigation session.…”
Section: Resultsmentioning
confidence: 99%
“…However, for this study, we are only interested in a subset of them that can be considered actual navigation sessions on the university campus. Previous studies have shown that the app is often used for looking up routes ahead of time and off campus, e.g., from their home or while riding the bus [ 30 ].…”
Section: Methodsmentioning
confidence: 99%